Outcome of uterine rupture and associated factors in Yirgalem general and teaching hospital, southern Ethiopia: a cross-sectional study - Achamyelesh Gebretsadik; Hailemichael Hagos; Kebede Tefera (BMC, 2020)
Abstract Background The occurrence of uterine rupture has dropped significantly in high income countries. It continues, however, to be a major public and clinical health problem in low income countries including Ethiopia. Aim of this study was to assess management outcomes of uterine rupture and associated factors in Yirgalem General and Teaching Hospital in South Ethiopia. Methods Institution-based cross-sectional study was conducted to examine medical records of women with uterine rupture between January 1, 2012, and Decem"ber 31, 2017. Data were collected based on a checklist. Descriptive statistics and logistic regression analyses were performed. Results Incidence of uterine rupture was 345 in 13,500 live births (25.5 in 1000 live births) in the study period. Of these, 331 cases were included. Poor maternal outcome occurred in 224 (67.7%) women. There were 13 (3.7%) maternal deaths and 320 (96.7%) stillbirths. Wound site infection (131; 39.6%) and anemia (129; 39%) were the most common post-operative complications. Prolonged duration of labor (more than 24 h) (adjusted odds ratio (aOR) 3.6; 95% CI 1.7-7.4), women with sepsis on admission (aOR 2.9; 95% CI 1.4-6.1), hemoglobin level < 7 g/dl prior to surgical intervention (aOR 4.5; 95% CI 1.1-17.8), delayed surgical intervention after hospitalization (4 h or more before surgery) (aOR 3.8; 95% CI 1.8-8), women who did not receive blood transfusion (aOR 4.0; 95% CI 2.1-7.9) and prolonged intraoperative time (aOR 5.5; 95% CI 2.8-10.8) were all factors associated with poor maternal outcome of uterine rupture. Conclusion Poor maternal outcome of uterine rupture was high in the study area as compared to other studies. Proper management of anemia, prompt surgical treatment, proper labor progress monitoring, surgical skills, improved infection prevention, maximizing blood transfusion availability and improving the quality of maternal healthcare all play a significant role in reducing uterine rupture and enhancing the chance of good outcomes.